The effect of intrapreneurship and organizational factors on the innovation performance in hospital - Ekingen, E.; Ekemen M.A.; Yildiz A.; Korkmazer F. (Editura Lumen, 2018)
In the context of environmental uncertainty and competition, organizations are trying to find new ways to improve their performance. The development of novelties based on innovation, especially in the service sector, is the departure point for many organizations. Intrapreneurship and organizational structure are important factors for organizations to improve the innovation performance. In this study, it is aimed to investigate whether intrapreneurship and organizational factors influence the innovation performance. The data were collected from a hospital by means of intrapreneurship scale, organizational factors scale and innovation performance scale. According to the results of Structural Equation Model analysis, intrapreneurship has positive influences on innovation performance. Organizational factors directly and indirectly affect innovation performance. Moreover, intrapreneurship has mediation effect between organizational factors and innovation performance. Lastly, Intrapreneurship enhances the effect of organizational factors on innovation performance. © 2018, Expert Projects. All rights reserved.
Keywords: Hospital; Human resources; Innovation performance; Intrapreneurship; Organizational factors